Resonance generation of sum harmonic in static electric field - Venger, E.F.; Griban, V.M.; Melnichuk, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Using the group theory considerations, we investigate the nonlinear effect tensor (NET) for a crystal in a static electric field when a harmonic or the initial emission frequency approaches that of the excitonic absorption band. The dependence of additional terms in NET (resulting from the electric field applied) on the electric field components is found. Their form is shown to differ from that of usual NET. The results obtained are illustrated by considering the case of the D₂d crystal symmetry.